Co-developing a health promotion programme for indigenous youths in Brazil: A concept mapping report. - Paulo T C Jardim; Josiliane M Dias; Antonio J Grande; André B Veras; Érika K Ferri; Fatima A A Quadros; Clayton Peixoto; Francielle C S Botelho; Maria I M G Oliveira; Ieda M A V Dias; Majella O'Keeffe; Christelle Elia; et al. (PLoS ONE)
Background Latin America and the Caribbean Region are home to about 42 million Indigenous people, with about 900,000 living in Brazil. The little routinely collected population-level data from Indigenous communities in the region available shows stark inequities in health and well-being. There are 305 Indigenous ethnic groups, speaking 274 languages, spread across the remote national territory, who have endured long-lasting inequities related to poverty, poor health, and limited access to health care. Malnutrition and mental health are key concerns for young people. Building on our Indigenous communities-academic partnerships over the last two decades, we collaborated with young people from the Terena Indigenous ethnic group, village leaders, teachers, parents, and local health practitioners from the Polo Base (community health centres) to obtain their perspectives on important and feasible actions for a youth health promotion programme. Methods The report was conducted in the Tereré Village in Mato Grosso do Sul. Concept mapping, a participatory mixed method approach, was conducted in 7 workshops, 15 adults and 40 youths aged 9-17 years. Art-based concept mapping was used with 9 to 11 years old children (N = 20). Concept systems software was used to create concept maps, which were finalised during the workshops. Focused prompts related to factors that may influence the health and happiness of youths. The participatory method gave Terena youths a significant voice in shaping an agenda that can improve their health. Results Terena youths identified priority actions that clustered under 'Family', 'School', 'Education', 'Socio-economic circumstances', 'Respect' and 'Sport' in response to protecting happiness; and 'Nutrition pattern', 'Physical activity', 'Local environment', and 'Well-being' in response to having a healthy body. Through the participatory lens of concept mapping, youths articulated the interconnectedness of priority actions across these clusters such that behaviours (e.g. Nutrition pattern, drinking water, physical activity) and aspirations (being able to read, to have a good job) were recognised to be dependent on a wider ecology of factors (e.g. loss of eco-systems, parent-child relationships, student- teacher relationships, parental unemployment). In response to developing youth health, Terena adults suggested priority actions that clustered under 'Relationships', 'Health issues', 'Prevention at Polo Base', 'Access to health care', 'Communication with young people', 'Community life', 'Raising awareness' and 'School support'. Their priorities reflected the need for structural transformative actions (e.g. Polo Base and school staff working together) and for embedding actions to protect Indigenous culture (e.g. integrating their cultural knowledge into training programmes). Conclusions Concept maps of Indigenous youths emphasised the need for a health promotion programme that engages with the structural and social determinants of health to protect their happiness and health, whilst those of adults emphasised the need to address specific health issues through preventative care via a school-Polo Base collaboration. Investment in a co-developed school-Polo-Base health promotion programme, with intersectoral engagement, has potential for making Indigenous health systems responsive to the inequalities of youth health, to yield dividends for healthy ageing trajectories as well as for the health of the next generation.